SELEKSI DESAIN ROOF TANK CSTR UNTUK PLANT BIOGAS POME SETARA 700KW - Ridho Dwimansyah; Trisaksono Bagus Priambodo; Yusnitati (Jurnal Energi dan Lingkungan (Enerlink), 2020)
Indonesia is the largest palm oil producer in the world. In the process of its processing into Crude PalmOil (CPO), the palm oil processing industry produces various types of waste, including liquid wasteknown as Palm Oil Mill Effluent (POME). POME contains organic matter that is high enough so it mustbe processed before being discarded into the environment. During this time, POME is treated usinganaerobic ponds which are quite large and produce metana gas. Metanae gas has a high level ofemissions, but it potential to become an energy source if it is utilized. Therefore, BPPT in collaborationwith PT. Perkebunan Nusantara 5 built a biogas production pilot plant from POME equivalent to 700kWfor boiler fuel at PKS Sei Pagar, Kampar Regency, Riau Province. The process of converting POMEinto biogas uses Continuous Stirred Tank Reactor (CSTR) technology. The research aims to choosethe best roof tank design for CSTR. The method used is the Pahl and Beitz method and the House ofQuality. The result of the study are the best specification planning data, which is 1400 mm in diameterand the construction site position at a height of 15350 mm from the bottom of the reactor, with use aninternal support column, with the best variant chosen is the fixed roof type with dome shape.